2022
DOI: 10.3390/ijms232012187
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Sepiolite High-Performance Magnetorheological Polishing Fluid with Reduced Sedimentation

Abstract: A sedimentation-stable magnetorheological (MR) polishing slurry on the basis of ferrofluid, iron particles, Al2O3, and clay nanofiller in the form of sepiolite intended for MR polishing has been designed, prepared, and its polishing efficiency verified. Added clay substantially improved sedimentation stability of the slurry, decreasing its sedimentation rate to a quarter of its original value (1.8 to 0.45 mg s−1) while otherwise maintaining its good abrasive properties. The magnetisation curve measurement prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The casings of aluminum alloy electronic products are only 1–2 mm thick, requiring surface roughness to reach a few nanometers without any deformation, which traditional mechanical finishing methods find difficult to meet [ 10 , 11 ]. Magnetic field-assisted finishing has been proven to be a low-damage [ 12 , 13 , 14 , 15 ], ultra-precision grinding and polishing method [ 16 , 17 ] that can effectively perform planar finishing such as on glass [ 18 ], polymers [ 19 ], stainless steel [ 20 , 21 ], copper [ 22 , 23 ], and alloys [ 24 , 25 ]. Kataria et al developed a continuous flow magnetorheological fluid finishing process for the finishing of small holes of 6063 aluminum alloy, with a surface roughness from 7.3 µm to 10.5 nm [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The casings of aluminum alloy electronic products are only 1–2 mm thick, requiring surface roughness to reach a few nanometers without any deformation, which traditional mechanical finishing methods find difficult to meet [ 10 , 11 ]. Magnetic field-assisted finishing has been proven to be a low-damage [ 12 , 13 , 14 , 15 ], ultra-precision grinding and polishing method [ 16 , 17 ] that can effectively perform planar finishing such as on glass [ 18 ], polymers [ 19 ], stainless steel [ 20 , 21 ], copper [ 22 , 23 ], and alloys [ 24 , 25 ]. Kataria et al developed a continuous flow magnetorheological fluid finishing process for the finishing of small holes of 6063 aluminum alloy, with a surface roughness from 7.3 µm to 10.5 nm [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the magnetic field is removed, MRFs quickly return to the Newtonian fluid state. MRFs have millisecond response time and good real-time controllability, which makes them suitable for devices controlled by external magnetic fields, such as brakes (Vezys et al, 2018;Acharya et al, 2021), clutches (Akbari et al, 2022;Bira et al, 2022), dampers (Wang et al, 2021;Nordin et al, 2022) and polishing devices (Bai et al, 2019;Milde et al, 2022). However, the density of the magnetic particles is about 7 times bigger than the carrier fluid, the magnetic particles settle in the carrier fluid (Kaide et al, 2020;Su et al, 2020;Maurya and Sarkar, 2021;Zhu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al [ 17 , 18 ] prepared iron ore/sepiolite nanocomposite particles and incorporated them into carbonyl iron-based magnetorheological fluids, improving the dispersion and magnetorheological performance of the fluid. Milde R et al [ 19 ] produced a settling stable magnetorheological polishing slurry using sepiolite and Al 2 O 3 and showed that the addition of sepiolite significantly improved the settling stability of the abrasive solution, reducing the rate of settling to a quarter of the original rate, and that the system was able to maintain long-term stability. However, most research efforts have focused on the shear yield strength and sedimentation stability of magnetorheological materials, with limited investigation into the influence of clay minerals on the normal force in magnetorheological systems, and the study of sepiolite on the normal force remains particularly poor.…”
Section: Introductionmentioning
confidence: 99%